Introduction to A Citizen Legislature by Ernest Callenbach and Michael Philips - STONE, PETER (Imprint Academic, 2008)
In 1997, I was a graduate student in the Political Science Department at the University of Rochester. Like most graduate students, I was always on the lookout for ways to earn a little extra money. For this reason, I became very excited when I learned of a new research project the department was conducting that summer. A wealthy benefactor had left the department a fairly large sum of money, to be spent investigating various proposals to amend the U.S. Constitution. Graduate students were invited to apply for that money. All you needed to get some was a decent idea to investigate?an idea regarding how our Constitution could be improved.
A Citizen Legislature/A People's Parliament
PUBLISHED
Keywords: Sortition; Lotteries; Random Selection; Congress; Descriptive Representation